2014
DOI: 10.1007/8904_2014_310
|View full text |Cite
|
Sign up to set email alerts
|

Fabry Disease: Multidisciplinary Evaluation After 10 Years of Treatment with Agalsidase Beta

Abstract: Fabry disease is an X linked disorder of metabolism due to deficient a-galactosidase A activity. Enzyme replacement therapy (ERT) with agalsidase Beta was approved by EMA in FDA in 2003. Patients and methods: Six patients were enrolled. Baseline data was measured for renal, cardiac, and cerebrovascular functioning. We compared baseline quality of life scales with the current results. These parameters were assessed during the 10 years of follow-up period.Results: Before ERT four patients showed normal eGFR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…A recent cohort study of adults in England by Anderson et al found that time on agalsidase alfa or agalsidase beta ERT was significantly associated with a reduction in LVMI as well as reduced risk of proteinuria and, among those without baseline proteinuria, a small increase in eGFR [28] . Another recent study by Juan et al of six patients in Argentina with mild disease at baseline found that after 10 years of agalsidase beta ERT, no patients had a reduction in eGFR or progression to LVH [29] . Results of other studies suggest that long-term agalsidase beta delays the time to morbidity and death [10] , [20] , although another study suggested no difference in event rate in patients with advanced disease at baseline versus an untreated control group [30] .…”
Section: Resultsmentioning
confidence: 93%
“…A recent cohort study of adults in England by Anderson et al found that time on agalsidase alfa or agalsidase beta ERT was significantly associated with a reduction in LVMI as well as reduced risk of proteinuria and, among those without baseline proteinuria, a small increase in eGFR [28] . Another recent study by Juan et al of six patients in Argentina with mild disease at baseline found that after 10 years of agalsidase beta ERT, no patients had a reduction in eGFR or progression to LVH [29] . Results of other studies suggest that long-term agalsidase beta delays the time to morbidity and death [10] , [20] , although another study suggested no difference in event rate in patients with advanced disease at baseline versus an untreated control group [30] .…”
Section: Resultsmentioning
confidence: 93%
“…In MG populations, the observation that agalsidase beta had a stabilizing effect on eGFR was consistently reported in 12 publications (one RCT with open-label extension [149] and two further open-label extensions in the same patients [150,157] and one single-arm CT publication [152] and eight OS publications [159,163,165,175,177,180,181,188]). Two publications reported different effects of agalsidase beta dose reduction on eGFR: one OS publication reported a statistically significant decrease (105 patients followed for 8–16 months) [181], whereas an RCT observed no effect (52 patients followed for 12 months or longer) [176].…”
Section: Resultsmentioning
confidence: 95%
“…One OS publication reported a statistically significant decrease in proteinuria with agalsidase beta in combination with paricalcitol [188]. One open-label extension of a placebo-controlled RCT [157] and four OS publications [159,160,165,181] reported no statistically significant change in proteinuria or albuminuria. In an RCT [176] and another OS publication [181], agalsidase beta therapy at a dose of 0.2 mg/kg EOW or with a dose reduction to 0.3–0.5 mg/kg EOW did not result in statistically significant changes in proteinuria and albuminuria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations